Pioneers of goodwill - Hunting, Harold B. (Friendship Press, 1929)
John Eliot of Roxbury.--Henry Melchior Muhlenberg.--Junipero Serra.--Henry Benjamin Whipple.--Samuel Chapman Armstrong.--Lucy Laney.--Sheldon Jackson.--Hudson Struck.--Frank Higgins.--Cora Wilson Stewart.--Roswell Bates.--Arthur Nash